Peran Suami Istri yang bekerja dalam Membangun Keluarga Sakinah Perspektif Teori Qira’ah Mubadalah Abdul Kodir - Any Sani’atin (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
A sakinah family is the dream of all married couples. Forming a sakinah family is not something that is not easy to achieve, especially in families who are both busy working. Nowadays, household management issues experience dynamics in various family segments. Various families have different perspectives on husband and wife relations in their families according to the environment or dynamics that occur in the family. This type of research includes library research. The data collection method used in this research is the documentation method of primary data sources. or secondary. The primary data source is data about the concept of the sakinah family and Faqihuddin Abdul Kodir's mubjadi theory. So the role of husband and wife in forming the Sakinah family is very important, both of them are very influential in terms of forming the child's character. The concept of mubdalam provides understanding and perspective in a relationship that embraces the spirit of cooperation and partnership on both parties. The issue of mubjadi is prioritizing relations between men and women both in the public and domestic spheres based on reciprocity, reciprocity and cooperation.